Building “terrorism studies” as an interdisciplinary space: addressing recurring issues in the study of terrorism - Youngman, Mark (Terrorism and political violence, 2020)
Over the years, there have been many debates regarding the state of research into terrorism and whether “terrorism studies” constitutes an academic discipline in its own right. Such reflections, coupled with the natural evolution of what is still a relatively new area of research, have arguably led to significant improvements in quality and rigour. At the same time, the status of terrorism studies itself remains somewhat ambiguous: it is both discussed as a distinct field and simultaneously evades criticism by pointing to the difficulties of defining its boundaries. There are undoubtedly a number of advantages to forming a separate discipline, which would go some way to helping the field address some of the recurring problems that terrorism research faces. However, this article ultimately argues that scholars are better served by deliberately moving in the other direction and developing the field as a space for interdisciplinary engagement.